Strategi Pengembangan Usaha Mikro Kecil dan Menengah di Provinsi Lampung - Novalita Novalita; Pipit Novila Sari (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
This research aims to arrange the correct and operational strategies for developing small and medium enterprises (SMEs) in Lampung Province. It also needs to be known and analyzed the SMEs profile. Data used is primary and secondary data. Pri- mary data obtained through field surveys, while secondary data obtained from various publi- cation sources. Method of analysis used is descriptive approach. Associated with the various problems faced by SMEs, there are some strategies needed to overcome them. To develop the SMEs is not only charged to the SMEs themselves but also supported by all stakeholders. The support expected to come from business associations, colleges, related agencies in Lampung Province. Moreover, government policy is needed to encourage SMEs development. The SMEs development in Lampung Province basically is the acceleration of the SMEs trans- formation from formation phase to stabilization phase.